Effects of Mindfulness-Based Cognitive Therapy on Peripheral Markers of Stress and Inflammation in Older-Adults With Depression and Anxiety: A Parallel Analysis of a Randomized Controlled Trial - Belliveau, Claudia; Nagy, Corina; Escobar, Sophia; Mechawar, Naguib; Turecki, Gustavo; Rej, Soham; Torres-Platas, Susana G. (Frontiers in Psychiatry, 2021)
Background: Depression and anxiety are prevalent in older-adults and often difficult to treat: up to 55% of patients are unresponsive to pharmacotherapy. Mindfulness-Based Cognitive Therapy (MBCT) is a promising treatment, however, its biological mechanisms remain unknown in older adults. Methods: We examined if, in older adults, decreased depression and anxiety symptoms after MBCT are associated with changes in the expression levels of C-Reactive Protein, Interleukin-1β, Monocyte Chemoattractant Protein-1 and mineralocorticoid receptor compared to treatment as usual. Older-adults (age ≥ 60) with depression and anxiety were randomized to MBCT or treatment as usual (TAU). Gene expression levels from blood samples were measured using quantitative polymerase chain reaction (n=37) at baseline and after 8-weeks of MBCT or TAU. Results: As previously published, we found a significant reduction in symptoms of depression and anxiety in geriatric participants following MBCT compared to treatment as usual F(2, 30) = 6.78, p < 0.05, partial η2 = 0.31. However, the expression levels of measured genes were not significantly different between groups and were not associated with changes in depression and anxiety symptoms. Conclusions: Our results suggest that the symptom reduction following MBCT in older adults may not be accompanied by changes in the stress-response and inflammatory pathways. Future research should address other potential biological alterations associated to MBCT that may be responsible for the reduction of symptoms.